This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given, 6X + Z = Y + W...............(1) X = Y + Z...........(2) Z = W - X..........(3 a) W = Z + X.........(3 b) Put (2) and (3 b) in (1) ~~ 6Y + 6Z + Z = Y + Z + X.....GIVEN THAT X+Y+Z=36 simplifying, 6Y + 7Z = 36........[A] CONSIDER X+Y+Z=36 and equation (2) says X=Y+Z ~~ Y+Z+Y+Z=36 Y + Z = 18.........[B] SIMPLIFYING "[A] & [B]",we get Z = -72 ; Y = 90 ; X = 18 ; W = -54 TO FIND:: XY + ZW == (18 * 90) + (-72 * -54) == 5508 .: THE ANSWER IS 5508.